Homocysteine concentration and adenosine A2A receptor production by peripheral blood mononuclear cells in coronary artery disease patients. Issue 16 (29th June 2020) - Deharo, Pierre; Marlinge, Marion; Guiol, Clair; Vairo, Donato; Fromonot, Julien; Mace, Patrick; Chefrour, Mohamed; Gastaldi, Marguerite; Bruzzese, Laurie; Gaubert, Melanie; Gaudry, Marine; Kipson, Nathalie; et al.
Abstract: Hyperhomocysteinemia is associated with coronary artery disease (CAD). The mechanistic aspects of this relationship are unclear. In CAD patients, homocysteine (HCy) concentration correlates with plasma level of adenosine that controls the coronary circulation via the activation of adenosine A2A receptors (A2A R). We addressed in CAD patients the relationship between HCy and A2A R production, and in cellulo the effect of HCy on A2A R function. 46 patients with CAD and 20 control healthy subjects were included. We evaluated A2A R production by peripheral blood mononuclear cells using Western blotting. We studied in cellulo (CEM human T cells) the effect of HCy on A2A R production as well as on basal and stimulated cAMP production following A2A R activation by an agonist‐like monoclonal antibody. HCy concentration was higher in CAD patients vs controls (median, range: 16.6 [7‐45] vs 8 [5‐12] µM, P  < 0.001). A2A R production was lower in patients vs controls (1.1[0.62‐1.6] vs 1.53[0.7‐1.9] arbitrary units, P  < 0.001). We observed a negative correlation between HCy concentration and A2A R production ( r  = −0.43; P  < 0.0001), with decreased A2A R production above 25 µM HCy. In cellulo, HCy inhibited A2A R production, as well as basal and stimulated cAMP production. In conclusion, HCy is negatively associated with A2A R production in CAD patients, as well as with A2A R and cAMP production in cellulo. The decrease in A2A R production and function, which is known to hamper coronary blood flow and promote inflammation, may support CAD pathogenesis.